DIGITAL MEDIA TO ENHANCE MUSEUM VISIT: EXPERIENCE IN DIGITIZING THE ROYAL MUSEUM OF KEDAH - Aeni Zuhana Saidin; Nassiriah Shaari (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Royal Museum of Kedah is the place that preserves historical artifacts belongs to Kedah Royalties. Transforming these ancient artifacts into digital media was an effort to enhance the museum visit, especially for the new generation to understand about one of the earliest histories in Malaysia. This is an initial phase in which the work was offered to be a class project for UUM’s multimedia student. As a result, four interactive digital applications were developed to fulfill the stated objective. Students’ challenges and experiences in conducting this project were discussed.